CARDIOVASCULAR COMPLICATIONS FROM COVID-19 MAY BE PREDICTED BY THE INCREASED LEVEL OF C-REACTIVE PROTEIN: A META-ANALYSIS. (April 2021) - Greca, Elona; Shah, Muhammad; Pandav, Krunal; Dedja, Dario; Hoxhaj, Ilda
Abstract : Objective: Current evidence suggests that the most common cardiovascular complications in the COVID-19 patients include acute myocardial injury, congestive heart failure (CHF), coronary artery disease (CAD), cardiac arrhythmias and thromboembolic events. Considering that the mechanism for myocardial injury is reported to result mainly from the direct viral involvement of cardiomyocytes and the effects of systemic inflammation, our scope is to evaluate the relation of the increased level of C-Reactive Protein (CRP) and the cardiovascular complications due to COVID-19. Design and method: We conducted a systematic literature search on various databases such as PubMed, Web of Science and Scopus to identify the relevant articles. We included studies published until September 2020. The receiver operating characteristic (ROC) curve was utilized to analyze the prognostic ability of CRP in the cardio-vascular complications from COVID-19. Subgroup and sensitivity analyses were performed. Heterogeneity was assessed using Cochran's Q test and I2 test. The presence of publication bias was evaluated by visual inspection of the symmetry in funnel plots Results: Nineteen studies met the inclusion criteria with more than 10, 630 participants. Subgroup analysis of the clinical classification included acute myocardial injury, CHF, CAD and thromboembolic events. The ROC curve shows that AUC (CHF)=85% (95% CI of 0.598 to 1); AUC (CAD)=81% (95% CI of 05.44 to 1); AUC (Thromboembolic events)=100% (95% CI of 1 to 1). The Kaplan-Meier curve and the log-rank test were applied to further assess the potential risk factors associated with the progression of cardiovascular complications from COVID-19. The Youden index was implemented to set cutoff values. Data analysis was conducted using SPSS 23.0 software. Figure. No caption available. Conclusions: This meta-analysis implies that CRP could be a valuable marker to anticipate the cardiovascular complications from COVID-19. Further evidence based research is mandated for the evaluation of the prognostic role of CRP in these patients.